1982
DOI: 10.1002/art.1780251220
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian artery thrombosis mimicking the aortic arch syndrome in systemic lupus erythematosus

Abstract: Lesions of the aorta and its main branches have rarely been described in systemic lupus erythematosus (SLE) (1,2). Arteriolar and postcapillary venular lesions predominate. The vasculitis of both large and small caliber vessels is thought to be caused by endothelial cell injury secondary to immune complex deposition ( 3 ) . The following patient with undiagnosed active SLE had left hand digital ischemia, and her left arm arterial pulses were absent due to thrombosis of the subclavian and brachial arteries.Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The role of tiopronin as a useful disease-remittive drug in rheumatoid arthritis (RA) has been established in clinical trials (1)(2)(3). Pasero et al (4), in a multicenter trial comparing tiopronin treatment with D-penicillamine treatment, have demonstrated comparable efficacy.…”
Section: Nephirotic Syndrome Induced By Tiopronin: Association With Tmentioning
confidence: 99%
“…The role of tiopronin as a useful disease-remittive drug in rheumatoid arthritis (RA) has been established in clinical trials (1)(2)(3). Pasero et al (4), in a multicenter trial comparing tiopronin treatment with D-penicillamine treatment, have demonstrated comparable efficacy.…”
Section: Nephirotic Syndrome Induced By Tiopronin: Association With Tmentioning
confidence: 99%
“…Lessof and Glynn had documented such a case many years earlier that also had demonstrated a false‐positive test for syphilis 25 . Ferrante et al 26 and Asherson et al 27 then also documented similar patients.…”
Section: Upper‐limb Occlusionsmentioning
confidence: 91%
“…During the following years, more studies on large arterial occlusions and gangrene in SLE patients with aPLs were published 102,103. In addition, an aortic arch syndrome and SLE were also observed,104-106 whereas a positive testing for aPLs was found,105 including occlusions of the abdominal aorta in aPL-positive patients 107,108. Since the first report by Hughes in 1983,109 the cerebral symptomatics in APS patients have become more and more important.…”
Section: Aps and Vaso-ischemic (Occlusive) Diseases With Neuropsychiamentioning
confidence: 99%